Development of Perovskite Oxide‐Based Electrocatalysts for Oxygen Evolution Reaction - Liu, Dong; Zhou, Pengfei; Bai, Haoyun; Ai, Haoqiang; Du, Xinyu; Chen, Mingpeng; Liu, Di; Ip, Weng Fai; Lo, Kin Ho; Kwok, Chi Tat; Chen, Shi; Wang, Shuangpeng; et al. (Small (Weinheim an der Bergstrasse, Germany), 2021)
Perovskite oxides are studied as electrocatalysts for oxygen evolution reactions (OER) because of their low cost, tunable structure, high stability, and good catalytic activity. However, there are two main challenges for most perovskite oxides to be efficient in OER, namely less active sites and low electrical conductivity, leading to limited catalytic performance. To overcome these intrinsic obstacles, various strategies are developed to enhance their catalytic activities in OER. In this review, the recent developments of these strategies is comprehensively summarized and systematically discussed, including composition engineering, crystal facet control, morphology modulation, defect engineering, and hybridization. Finally, perspectives on the design of perovskite oxide‐based electrocatalysts for practical applications in OER are given. The review systematically summarizes the recent developments of perovskite oxides for efficient electrocatalytic oxygen evolution reaction (OER) in both experimental and theoretical studies. Various strategies to improve the OER catalytic performance are carefully discussed, including composition engineering, crystal facet control, morphology modulation, defect engineering, and hybridization.